2012
DOI: 10.1039/c2ay25418b
|View full text |Cite|
|
Sign up to set email alerts
|

Novel 8,9-dihydroxy-7-methyl-12H-benzothiazolo[2,3-b]quinazolin-12-one multiwalled carbon nanotubes paste electrode for simultaneous determination of ascorbic acid, acetaminophen and tryptophan

Abstract: The electrooxidation of ascorbic acid (AA), acetaminophen (AC), tryptophan (Trp), and their mixture has been studied using an 8,9-dihydroxy-7-methyl-12H-benzothiazolo[2,3-b]quinazolin-12-one modified carbon nanotubes paste electrode and cyclic voltammetry, chronoamperometry, electrochemical impedance spectroscopy and square wave voltammetry methods. The sensor exhibited potent and persistent electron mediating behavior followed by well separated oxidation peaks towards AA, AC and Trp with activation overpotent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Fig. Referring to the analytical performances of some recently published reports [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] (Table 2), it is found that the obtained detection limit in this work is lower than other modified electrodes, which is likely related that MWCNT-CTAB have high electrocatalytic and surface area effects. 6(b)).…”
Section: Linearity Range and Detection Limit Using Voltammetrymentioning
confidence: 66%
“…Fig. Referring to the analytical performances of some recently published reports [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] (Table 2), it is found that the obtained detection limit in this work is lower than other modified electrodes, which is likely related that MWCNT-CTAB have high electrocatalytic and surface area effects. 6(b)).…”
Section: Linearity Range and Detection Limit Using Voltammetrymentioning
confidence: 66%
“…1, which is related to omeprazole. [48][49][50][51][52][53][54][55][56][57][58][59][60][61] As a continuation of previous work, 62-68 the use of MWCNTs and the ionic liquid BMIMPF 6 , based on their synergy to form a novel composite thin-film material at a GCE, is described herein for the electrochemical determination of LNS in commercial tablet form. 1 LNS is effective in the treatment of various peptic diseases, including duodenal ulcers, peptic ulcer, reflux esophagitis and ELECTROCHEMICAL BEHAVIOR AND DETERMINATION OF LANSOPRAZOLE 41 ing to the literature, 47 MWCNTs are untangled after treatment with RTILs, mainly because of cross-linking of the nanotube bundles mediated by local molecular ordering of the RTIL resulting from "cation-π" interactions between imidazolium and nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, noble metal nanoparticles have been the subject of focused research due to their unique optical, electronic, mechanical, magnetic, and chemical properties that are significantly different from those of bulk materials [1]. From different carbon-based nanomaterials, carbon nanotubes can be used to promote electron transfer reactions when used as electrode material [2][3][4][5][6] in electrochemical devices, electrocatalysis, and electroanalysis processes due to their significant mechanical strength, high electrical conductivity, high surface area, good chemical stability, as well as relative chemical inertness in most electrolyte solutions, and a wide operation potential [7][8][9][10][11][12][13][14]. Many other applications of nanoparticles are now known such as sensor in nanosize containing Mnnanoparticles decorated organo-functionalized nanosized SiO 2 -Al 2 O 3 mixed-oxide support was developed as a new electro catalysis for oxidation of organic compounds such as many important drugs [6].…”
Section: Introductionmentioning
confidence: 99%